STUDI AWAL PADA PREPARASI KATALIS BERBASIS LEMPUNG BERPILAR UNTUK REAKSI ETANOL MENJADI GASOLINE (ETG) - Nino Rinaldi; Adid Adep Dwiatmoko (Jurnal Kimia Terapan Indonesia, 2011)
Research on catalytic reaction of ethanol to gasoline (ETG) was investigated in this study. The catalyst with a high acidity is required for the ETG reaction. Therefore, this study focused on the catalyst preparation of ETG reaction by using natural clays which prepared by the pillarization techniquewithseveral metal oxides, such as:AI, Zr, Fe and Cr as the pillared. The prepared of pillared clay were characterized by x-ray diffraction, specific surface area and pore distribution (BET) measurements and  catalytic activity testing on the ETG reaction. It is observed that after the pillarization; the surface area and basal spacing (d001) of the natural clays were significantly increased. thus the   ptllarization process was successfully prepared on natural clay. However,the acidity of theprepared ofpillared clay is still  lower,probably due to the cations between layers of the natural clay were not homogeneous, thus although the pillarization process was happen but still not completely. Moreover, IR measurement showed only the acid type of Lewis is increased after the pillarization. Thistype is not favorable for the ETG reaction, and thus only the lower hydrocarbon products (<Cl2) were observed after the ETG reaction, even aromatics and cyclic hydrocarboncompounds wereobtainedKeyword : preparation, pillared clay, catalyst, ETG reaction.